Exploring the Relationships Among Experiences in Nature, Wellbeing, and Stewardship During the COVID-19 Pandemic - Heilmayr, Dietlinde; Baranski, Erica N.; Miller, Travis J. (Frontiers in Sustainable Cities, 2022)
The COVID-19 pandemic brought sudden and dramatic changes to our daily lives. From shifting to remote work, to following shelter-in-place orders, to increased concerns about the health and wellbeing of one's self and family, individuals were required to make changes to their daily habits and to find new methods of coping with stress and maintaining wellbeing. In the present study, we surveyed participants in the United States (N = 192) with open-ended questions and individual difference measures to capture how changes to daily life due to the COVID-19 pandemic affected individuals' engagement with the outdoors. Specifically, using descriptive and inferential statistics, we (1) describe how people experienced the outdoors during the beginning stages of the COVID-19 pandemic; (2) evaluate how individuals' experiences outdoors relate to individual differences; and (3) report whether environmental experiences and COVID-19 concern relate to whether individuals chose to donate their participation payment to The Trust for Public Land, to the Center for Disease Control's COVID-19 fund, or to keep the payment for themselves in the form of a gift card. This work enhances our understanding of how the pandemic affected the relationship between people and the outdoors and contributes to knowledge about how nature can be used to help individuals and communities during times of crisis.